Thai pigs and cattle production, genetic diversity of livestock and strategies for preserving animal genetic resources - Rangsun Charoensook (2018)
This paper reviews the current situation of livestock production in Thailand, genetic diversity and evaluation, as well as management strategies for animal genetic resources focusing on pigs and cattle. Sustainable conservation of indigenous livestock as a genetic resource and vital components within the agricultural biodiversity domain is a great challenge as well as an asset for the future development of livestock production in Thailand. © 2013 by Maejo University, San Sai, Chiang Mai, 50290 Thailand. Reproduction is permitted for noncommercial purposes.